Social Media as a Means of Tourism Promotion by the Department of Tourism, Culture, Youth, and Sports of Palangka Raya City - Peni Lisari; Kadek Sukiada; Budi Purnomo; Muthia Farida (IAHN-TP Palangka Raya, 2026)
The use of social media as means for promotion has been widely used in the tourism industry. One of the departments whose responsibility for promoting tourism is Department of Tourism, Culture, Youth and Sports (Disparbudpora) of Palangka Raya City. In relation to its main responsibility, there must be a specific management on the use of social media for tourism promotion. This research objective was to investigate the social media patterns a means of tourism promotion by Disparbudpora Palangka Raya. This descriptive qualitative research employed observation, interviews, documentation and literature to help collect the data. The informants were the social media staffs of Disparbudpora and social media followers of Disparbudpora accounts. The research results showed that the pattern of promotion using social media carried out by Disparbudpora consisted of four stages, including content creation, platform determination, program implementation, monitoring and evaluation, and the four mix promotions carried out were advertising, sales promotion, public relations and publicity, and direct marketing. Keywords: Social Media, Tourism Promotion, Department of Tourism